1992
DOI: 10.1002/hep.1840160604
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Oval–Type Cells in Hepatitis B Virus—Associated Human Hepatocarcinogenesis

Abstract: Proliferation of a new population of epithelial cells with distinct structure, as well as cytokeratin and alpha-fetoprotein expression, was observed in nonneoplastic liver tissues from 14 cases (13 hepatitis B virus-positive) of human hepatocellular carcinoma. These cells were characterized by oval nuclei; scant, pale cytoplasm; small cell size; and cross-reaction with a monoclonal antibody against rat oval cells. These putative human oval cells were strongly positive for cytokeratin 19 and displayed considera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
101
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(105 citation statements)
references
References 10 publications
3
101
0
1
Order By: Relevance
“…Although not all cases of hepatocellular carcinoma with ezrin expression had CK19 expression, these results suggest that at least some cases of hepatocellular carcinoma with ezrin expression are derived from hepatic progenitor cells. The association of ezrin expression with high serum AFP, which is also a marker of progenitor cell compartments, 25 is compatible with a progenitor cell origin for these tumors. The fact that some cases of hepatocellular carcinoma with ezrin expression showed negative CK19 expression may be due to the fact that cases of hepatocellular carcinoma that are consistent with a progenitor cell origin may not necessarily have positive CK19 expression, as previously described.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Although not all cases of hepatocellular carcinoma with ezrin expression had CK19 expression, these results suggest that at least some cases of hepatocellular carcinoma with ezrin expression are derived from hepatic progenitor cells. The association of ezrin expression with high serum AFP, which is also a marker of progenitor cell compartments, 25 is compatible with a progenitor cell origin for these tumors. The fact that some cases of hepatocellular carcinoma with ezrin expression showed negative CK19 expression may be due to the fact that cases of hepatocellular carcinoma that are consistent with a progenitor cell origin may not necessarily have positive CK19 expression, as previously described.…”
Section: Discussionmentioning
confidence: 68%
“…The fact that some cases of hepatocellular carcinoma with ezrin expression showed negative CK19 expression may be due to the fact that cases of hepatocellular carcinoma that are consistent with a progenitor cell origin may not necessarily have positive CK19 expression, as previously described. 10 Several studies using detailed immunophenotyping, with CK19, CK7, or OV6 for example, showed that 28-50% of cases of hepatocellular carcinoma derive from progenitor cells and their progeny, 9,11,25,26 a frequency that is compatible with cases of hepatocellular carcinoma with ezrin expression. No specific marker for hepatic progenitor cell compartment has yet been described.…”
Section: Discussionmentioning
confidence: 99%
“…Novel cell types reminiscent of progenitor (stem)-like cells have been identified in human liver. 29,32,33 De Vos et al found small numbers of cells by electron microscopy that were difficult to detect by routine light microscopy. 29 Similarly, Ruck et al, 32 reported similar small numbers of oval-like cells in hepatoblastoma tumors, which they speculated might be precursors of ductular biliary cells and hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Given the association between experimental models of hepatotoxicity and carcinogenesis, it is not surprising that oval cells have been identified in acute and chronic human liver pathologies including HBV/ HCV infection, hemachromatosis and alcoholic liver disease. [32][33][34][35][36][37][38][39] …”
Section: Factors That Regulate Oval Cell-mediated Liver Regenerationmentioning
confidence: 99%